Evaluation of Primigravida Women’s Childbirth Self-efficacy at Al-Elwea Maternity Hospital in Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2021)
Abstract: Pregnant women who believe themselves have capabilities to cope with childbirth, they feel ableto control labor stress. On the other hand, if they believe themselves uncappable to cope with labor, theycannot control labor stress and may choose cesarean delivery.Objectives: To evaluate women’s self-efficacy of childbirth and find out the association between women’sself-efficacy and study variables.Methods: Descriptive study of non-probability (purposive sample) was used to collect the data from (100)women. A pilot-test was conducted to determine the reliability of the questionnaire. Data were analyzedthrough the use of SPSS.Results: The higher percentage of women’s age was (20-29) years graduated from secondary school. Aboutone-third of them in gestational age 32 weeks. More than two-thirds of them are preferred cesarean birth.They have a low childbirth self-efficacy. There are significant differences between women’s age, education,occupation, delivery preference, and childbirth self-efficacy.Conclusion: This study finds that primigravida women have low childbirth self-efficacy, and there aresignificant differences between women’s self-efficacy with the demographic and reproductive variables.Recommendations: Primigravida women need prenatal education and encouragement regarding labor toincrease their believe of own capability to control and cope with labor stress.